2023
DOI: 10.1177/23779608231158419
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators Affecting the Uptake of COVID-19 Vaccines: A Qualitative Perspective of Frontline Nurses in Namibia

Abstract: Aim Vaccinations remain one of the most effective measures to prevent and control the spread of COVID-19, while also reducing hospitalizations and deaths, yet many are unwilling to be vaccinated. This study explores the barriers and facilitators affecting the uptake of COVID-19 vaccines among frontline nurses. Design A qualitative, explorative, descriptive, and contextual research strategy was employed. Methods A sample of 15 nurses were selected via purposeful sampling to the point of data saturation. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…In this review, most of these studies reported HCWs’ hesitation to accept the COVID-19 vaccines on the African continent. A qualitative study conducted by Ashipala and colleagues [ 63 ] did not provide information on nurses’ uptake of COVID-19 vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, most of these studies reported HCWs’ hesitation to accept the COVID-19 vaccines on the African continent. A qualitative study conducted by Ashipala and colleagues [ 63 ] did not provide information on nurses’ uptake of COVID-19 vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…The perception of susceptibility to contracting COVID-19 among HCWs was mentioned as both a barrier and a facilitator for vaccine uptake. HCWs who perceived themselves to be at a higher risk of contracting COVID-19 [ 25 , 47 , 59 , 63 , 88 , 92 ] were more willing to get vaccinated compared to those who perceived themselves to have a low risk [ 23 , 66 , 67 , 78 , 91 ]. HCWs who believed they needed the vaccine for protection were more likely to get vaccinated than those who relied on their immune system to prevent infection [ 65 , 68 , 76 , 77 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance confirmability, the researcher's differing viewpoints on the themes were discussed and resolved with the assistance of the second author, who had qualitative expertise. The study followed the Consolidated Criteria for Reporting Qualitative Research Checklist (COREQ) to guarantee comprehensive documentation of the methods used and outcomes attained (Ashipala et al., 2023 ). To ensure transferability, a clear and precise depiction of the study population and research procedure is provided, which will enable others to follow the research trajectory and key analytical determinations.…”
Section: Methodsmentioning
confidence: 99%
“…Research Checklist (COREQ) to guarantee comprehensive documentation of the methods used and outcomes attained (Ashipala et al, 2023). To ensure transferability, a clear and precise depiction of the study population and research procedure is provided, which will enable others to follow the research trajectory and key analytical determinations.…”
Section: Trustworthinessmentioning
confidence: 99%